2012
DOI: 10.3390/s120505608
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Optical Activation Mechanisms of Nanospring-Based Chemiresistors

Abstract: Chemiresistors (conductometric sensor) were fabricated on the basis of novel nanomaterials—silica nanosprings ALD coated with ZnO. The effects of high temperature and UV illumination on the electronic and gas sensing properties of chemiresistors are reported. For the thermally activated chemiresistors, a discrimination mechanism was developed and an integrated sensor-array for simultaneous real-time resistance scans was built. The integrated sensor response was tested using linear discriminant analysis (LDA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…On the other hand, these devices are necessary for acquiring a fundamental understanding of corresponding physical and chemical processes triggered by surface-molecule interactions (chemisorption), as well as for interpreting the electrical transport properties of gas sensitive materials. The use of metal oxide nanocrystalline thin films, as well as other more complex nano-morphologies, as the gas sensitive layers in chemiresistors is well documented [1][2][3][4][5][6][7][8][9][10][11]. These studies demonstrated that if the dimensions of the nanostructures are comparable to the characteristic length scales of surface interactions, the sensor will be more responsive to changes in surface stoichiometry.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…On the other hand, these devices are necessary for acquiring a fundamental understanding of corresponding physical and chemical processes triggered by surface-molecule interactions (chemisorption), as well as for interpreting the electrical transport properties of gas sensitive materials. The use of metal oxide nanocrystalline thin films, as well as other more complex nano-morphologies, as the gas sensitive layers in chemiresistors is well documented [1][2][3][4][5][6][7][8][9][10][11]. These studies demonstrated that if the dimensions of the nanostructures are comparable to the characteristic length scales of surface interactions, the sensor will be more responsive to changes in surface stoichiometry.…”
Section: Introductionmentioning
confidence: 86%
“…The effects of chemisorption on the electrical transport properties of metal oxides is well documented [1][2][3][4][5][6][7][8][9][10][11][19][20][21][22]. In the case of ZnO 1- , where the surface is oxygen deficient, the surface readily oxidized in ambient air to obtain the ideal surface stoichiometry of ZnO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact potential can be viewed as a tunneling barrier to electrons, which in our case is modulated by the oxidation of the analyte. It is well known that the surface area and the surface defects are crucial for a high sensitivity given that the ionization happens primarily on the edges and corners of the nanocrystals [4–6]. This explains the superior sensitivity of the ALD fabricated polycrystalline oxide films.…”
Section: Signal Processing and Pattern Recognitionmentioning
confidence: 99%
“…A SAW device with high sensitivity, fast response and low cost can be used in kinds of applications [1,2] such as indoor air measurement, food product quality control, environmental monitoring [3,4], military applications, and national security. Comparing with other microsensors such as potentiometric charge sensitive devices, thermally based detectors, and chemiresistors [5,6], an electronic nose device has higher sensitivity, smaller size and cheaper cost. The advantage of high sensitivity results from the fact that surface acoustic waves are mostly confined to the piezoelectric substrate surface within one or two wavelengths and thus are very sensitive to changes of sensitive film properties such as the surface electrical conductivity, elastic moduli, mass, and permittivity when exposed to target gases.…”
Section: Introductionmentioning
confidence: 99%